2013
DOI: 10.3892/br.2013.134
|View full text |Cite
|
Sign up to set email alerts
|

Association of methylenetetrahydrofolate reductase C677T and A1298C polymorphisms with colorectal cancer risk: A meta-analysis

Abstract: Abstract. Colorectal cancer (CRC) is one of the most common types of cancer worldwide and a leading cause of cancer-related mortality. This meta-analysis was conducted to determine the effect of methylenetetrahydrofolate reductase (MTHFR) mutants on the risk of CRC. A literature search was conducted on PubMed, Medline and the China National Knowledge Infrastructure (CNKI) databases. Eligible studies were collected based on rigorous criteria of inclusion. The pooled odds ratios (ORs) with 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 59 publications
5
30
0
2
Order By: Relevance
“…Our result of a potentially protective effect of the MTHFR rs1801133 CT/TT genotype on CRC is in accordance with previous findings21222324. The primary function of MTHFR is to catalyse the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate25.…”
Section: Discussionsupporting
confidence: 92%
“…Our result of a potentially protective effect of the MTHFR rs1801133 CT/TT genotype on CRC is in accordance with previous findings21222324. The primary function of MTHFR is to catalyse the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate25.…”
Section: Discussionsupporting
confidence: 92%
“…Homozygosity for the T allele is associated with reduced enzyme activity (up to 70 % lower), around 20-25 % lower serum folate and higher plasma total homocysteine concentrations compared with the 677CC genotype (Jacques et al, 1996;Davis et al, 2005;Hustad et al, 2007). Meta-analyses have shown that the 677TT genotype is associated with a reduced risk of colorectal cancer (Huang et al, 2007;Zhao et al, 2013), but with an increased risk of neural tube defect (NTD)affected pregnancies (Vollset and Botto, 2005), pregnancy complications (Nelen et al, 2000;Kosmas et al, 2004), stroke (Casas et al, 2005;Cronin et al, 2005), schizophrenia (Muntjewerff et al, 2006;Gilbody et al, 2007) and depression (Gilbody et al, 2007). Reduced global DNA methylation was shown in individuals with the 677TT genotype in one study (Friso et al, 2002); however, the evidence is inconsistent, as this was not confirmed in two other studies (Shelnutt et al, 2004;Davis et al, 2005).…”
Section: Effects Of Genotypesmentioning
confidence: 99%
“…Some results have reported that the 677TT genotype could cause a considerable risk reduction of CRC. In high folate intake cases, the risk of CRC risk is reduced for both MTHFR 677CC and 677TT genotypes [30].…”
Section: Discussionmentioning
confidence: 99%